2016
DOI: 10.1172/jci.insight.86082
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of FAK and tyrosine kinase inhibition in Ph+ B-ALL

Abstract: BCR-ABL1+ B progenitor acute lymphoblastic leukemia (Ph+ B-ALL) is an aggressive disease that frequently responds poorly to currently available therapies. Alterations in IKZF1, which encodes the lymphoid transcription factor Ikaros, are present in over 80% of Ph+ ALL and are associated with a stem cell–like phenotype, aberrant adhesion molecule expression and signaling, leukemic cell adhesion to the bone marrow stem cell niche, and poor outcome. Here, we show that FAK1 is upregulated in Ph+ B-ALL with further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 38 publications
5
41
0
1
Order By: Relevance
“…FAK is a key effector of integrin signaling that is repressed by IKAROS in large pre-B cells (Joshi et al 2014). A combination therapy with inhibitors for the ABL and FAK shows promise in reducing adhesion properties and leukemia-initiating frequencies in human B-ALL (Churchman et al 2016). Thus, previously established protocols combined with recent insights into the IKAROS-based signaling and transcriptional networks in pre-B cells can provide more effective approaches to target high-risk B-ALL.…”
Section: Ikaros and Polycomb Repression Of A B-cell-epithelial Transimentioning
confidence: 99%
“…FAK is a key effector of integrin signaling that is repressed by IKAROS in large pre-B cells (Joshi et al 2014). A combination therapy with inhibitors for the ABL and FAK shows promise in reducing adhesion properties and leukemia-initiating frequencies in human B-ALL (Churchman et al 2016). Thus, previously established protocols combined with recent insights into the IKAROS-based signaling and transcriptional networks in pre-B cells can provide more effective approaches to target high-risk B-ALL.…”
Section: Ikaros and Polycomb Repression Of A B-cell-epithelial Transimentioning
confidence: 99%
“…We and others have shown that the focal adhesion kinase (FAK) pathway is activated downstream of integrin signaling, and is activated in Ikaros-mutated BCR-ABL1 ALL (42, 54, 55). FAK serves to integrate a variety of cell surface signaling inputs, leading to downstream activation of gene expression and reorganization of cytoskeletal architecture.…”
Section: Targeting Adhesion Molecule Signaling In Ikaros Mutant All: mentioning
confidence: 99%
“…We systematically examined activation of FAK signaling pathways and the potential of FAK inhibition in a series of mouse and human cell models (54). Using phosphoproteomic analysis, we showed increased phosphorylation of FAK1, also known as Protein Tyrosine Kinase 2 (PTK2), and FAK2 (PTK2b) in Ikaros mutant tumors, and activation of FAK signaling as shown by elevated levels of p130Cas, a downstream target of FAK.…”
Section: Targeting Adhesion Molecule Signaling In Ikaros Mutant All: mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in a patient-derived xenograft model of mesothelioma showed that FAK inhibitor VS-4718 preferentially eliminated the cancer stem cells that were enriched following treatment with chemotherapeutic agents (11). VS-4718 treatment in combination with dasatinib prolonged survival in a model of B-ALL (12). Several FAK inhibitors, such as VS-4718, have entered clinical trials (NCT01849744, NCT02651727) in solid tumors.…”
Section: Introductionmentioning
confidence: 99%